Trends in maximum and minimum temperature in the Central Andes of Peru (Mantaro River Basin) - Trasmonte Soto, Grace Liliam (2006)
The Mantaro River Basin (34550,08 Km2) is located on the eastern slope of the central Peruvian Andes, between the coordinates 10º34’30’’S- 13º35’30’’S/ 73º55’00’’W- 76º40’30”W. This is a very complex basin due to its geomorphology, with almost 85% of its territory located above 3000 masl. This basin was chosen for an Integrated Local Assessment with a Climate Change perspective, because its strategic location. The Mantaro basin provides a constant supply of resources (water, energy and farming products) to Lima, the capital of Peru. This is the first effort made until now in this respect in our country. In this context, a linear trend analysis of observed temperature data (minimum and maximum) has been performed, using monthly and daily data for the1960-2002 period, provided by nine meteorological stations, with altitudes ranging from 3150 masl to 4413 masl.